(untitled) (Academia Journal of Medicine, 2021)
Background: The main problem is the diagnosis and treatment of combined closed abdominal trauma, accompanied by shock on the background of massive intra-abdominal bleeding with liver and spleen injuries. The hospital mortality rate for this type of pathology ranges from 17.3 to 72.7%. Methods: The treatment and outcomes of 539 patients with closed injuries of the abdominal organs in 2011 - 2021 were analyzed. Multi-stage ”damage control” surgical tactics in isolated and combined severe liver injuries is an effective method in unstable patients with the risk of coagulopathy and multiple organ failure. Results: Out of 539 patients with closed abdominal injuries, 269 (49.9%) were operated on. Of these, 131 (48.7%) had liver and spleen injuries. According to the localization of damage according to the Mooge classification, there were: liver grade I in 9 people, grade II in 18, grade III in 25, grade IV in 17, and grade V in 3 victims. Spleen ruptures were diagnosed as grade I in 6 patients, grade II in 15, grade III in 26, grade IV in 10, and grade V in 2 patients. Conclusion: A necessary component at the final stage of surgical intervention is intestinal decompression in order to conduct enteral tube feeding to correct hypermatabolism and prevent secondary systemic complications associated with emerging enteric insufficiency.